Pelvic Floor Health and Urinary Incontinence in Female Soccer Players: A Comparative Analysis Between Professionals and Physically Active Women: A Cross-Sectional Descriptive Protocol - Julia M. Sebastian-Rico; María Jesús Muñoz-Fernández; Luis Manuel Martínez-Aranda; África Calvo-Lluch; Manuel Ortega-Becerra (Diagnostics)
Background/Objectives: Urinary incontinence (UI), defined as the involuntary loss of urine, is common among female athletes. As more women engage in competitive sports, numerous studies have explored UI in young, nulliparous, and physically active women. The objectives of this study were (i) to analyze the prevalence, severity, and characteristics of UI in professional nulliparous female soccer players and (ii) to compare the status of the pelvic floor muscles (PFMs) between professional soccer players and physically active young women. Methods: This descriptive cross-sectional study included professional soccer players (n = 18) and physically active women (n = 14). UI was assessed using the ICIQ-SF questionnaire, and PFM function was evaluated through intracavitary examination using the PERFECT method. Additional data were collected on body composition and on urinary, bowel, and sexual health. Results: UI affected 35.7% of physically active women and 50% of professional soccer players. Stress urinary incontinence (SUI) was the most common type, present in 100% of affected soccer players and 60% of affected active women. The severity of UI was mostly mild, with no significant differences between groups. PFM assessment revealed deficiencies in control, relaxation, endurance, and rapid contractions, as well as difficulties performing an effective perineal locking (PL) maneuver during increased intra-abdominal pressure. Conclusions: These findings highlight the need for targeted programs focused on strengthening and educating athletes about their PFMs, aiming to prevent UI and improve both performance and quality of life. The study reinforces the importance of preventive strategies for pelvic floor health in sports.